English for specific purposes culture in Moroccan higher education: realities and challenges - Ayoub Ismaili Alaoui; Jihane El Moussaddar; Driss Marjane (Institute of Advanced Engineering and Science, 2026)
In some educational contexts, English for specific purposes (ESP) is perceived to better align with learners’ specific goals compared to general English (GE). In Morocco, higher education institutions have been increasingly offering ESP courses despite the little research on the extent to which those courses actually reflect an ESP culture. This research has so far focused only on individual initiatives or particular institutions. This study, however, set itself the more ambitious aim of investigating the existence of an ESP culture in six different Moroccan higher education institutions and identifying the constraints that hindered the development of this culture. The study used document analysis and semi-structured interviews as data collection instruments. A total of 63 English course documents from students were subjected to qualitative content analysis, followed by a thematic analysis of data collected from six interviews with English instructors. The data identified both ESP and GE approaches across the institutions in the study. However, ESP seemed to be higher in highly competitive and interdisciplinary institutions, whereas GE was higher in less competitive institutions with similar majors. GE practices persisted due to revealed challenges that hamper effective ESP implementation. These findings suggest that Moroccan higher education institutions generally lack a strong ESP culture. The apparent importance of ESP in Morocco does not extend to the level of adopting an explicitly articulated ESP curriculum.